2009
DOI: 10.1007/s00192-009-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in stress urinary incontinence 1 year after first delivery

Abstract: The new onset of SUI during pregnancy is an independent risk factor for SUI in the postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
3
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 34 publications
6
45
3
7
Order By: Relevance
“…There is no doubt that vaginal delivery is associated with urinary incontinence after childbirth and that the presence of UI during pregnancy can predispose to UI in the postpartum period (13). However, Huebner et al (2010) related that showed that the effects of pregnancy on the pelvic floor are different from those triggered after vaginal delivery (12).…”
Section: Discussionmentioning
confidence: 94%
“…There is no doubt that vaginal delivery is associated with urinary incontinence after childbirth and that the presence of UI during pregnancy can predispose to UI in the postpartum period (13). However, Huebner et al (2010) related that showed that the effects of pregnancy on the pelvic floor are different from those triggered after vaginal delivery (12).…”
Section: Discussionmentioning
confidence: 94%
“…Other authors have also observed that UI during pregnancy increases the risk of UI in the puerperium. A study conducted with primiparous women a year postpartum showed that women with UI during pregnancy were five times more likely to develop SUI (OR 5.79, CI 95% 2.79 -12) (24) . Another study included only primiparous women and found that participants with UI during pregnancy were 2.3 more likely to present UI six months postpartum (IC 95% 2.2 -2.4) (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Doğumdan sonraki beş yılda risk dört kez daha artar. 15,16 Birinci trimestrda Üİ prevalansı % 15 olup, gebe olmayan kadınlar ile eşittir. İkinci ve üçüncü trimestrda prevalans sırası ile % 35 ile % 40'a ulaşmaktadır.…”
Section: Pelvik Tabanunclassified
“…17 Ayrıca çok doğum yapan kadınlar tek doğum yapanlara göre, beyaz kadınlar siyah kadınlara göre daha fazla pelvik taban sorunları yaşamaktadır. 15,17 Vajinal doğum nedeniyle genellikle kaslarda, pelvik taban yapılarını destekleyen fasia ve ligamentlerde anlamlı olarak gerilme meydana gelmektedir. Bu yapılarda, anormal morfolojik ve fonksiyonel değişiklikler meydana gelebilmekte ve hatta bu değişiklikler geriye dönüşümsüz olabilmektedir.…”
Section: Pelvik Tabanunclassified